2015
DOI: 10.1016/j.radonc.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of stereotactic body radiation therapy for peripheral T2N0M0 non-small cell lung cancer with PTV < 100 cc using a continual reassessment method (JCOG0702)

Abstract: Key Words: phase I study, continual reassessment method, non-small cell lung cancer (NSCLC), stereotactic body radiotherapy, SBRT. Short running title: Previous presentationThis work was presented at the 55th Annual Meeting of the American Society for Radiation Oncology, September 22 -25, 2013 in Atlanta, GA. / 28Abstract Purpose: To estimate the maximum tolerated dose (MTD) and to determine the recommended dose (RD) of stereotactic body radiation therapy (SBRT) for peripheral T2N0M0 non-small cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…We previously reported the results for patients with PTV < 100cc, and the RD was 55 Gy (D 95 ) for these patients with PTV < 100 cc [9]. One of the reasons for the lower RD in this report may be the differences in the irradiated lung volume.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…We previously reported the results for patients with PTV < 100cc, and the RD was 55 Gy (D 95 ) for these patients with PTV < 100 cc [9]. One of the reasons for the lower RD in this report may be the differences in the irradiated lung volume.…”
Section: Discussionmentioning
confidence: 58%
“…The eligibility and exclusion criteria, the radiotherapy methods and the study design for the group with PTV ≥ 100 cc are the same as those previously reported for the group with PTV < 100cc [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve better local control, we chose to administer 55 Gy in four fractions prescribed at the dose covering 95% of the volume (D 95% ) of the planning target volume (PTV) as the dose and fraction schedule. This was determined to be the recommended dose for peripheral c-Stage IB NSCLC with PTV < 100 cc in a Phase I study of SBRT known as JCOG0702 (19). We also confirmed through simulation that further dose escalation would be difficult for c-Stage IA disease when considering the dose constraints of organs at risks.…”
Section: Introductionsupporting
confidence: 56%
“…On the other hand, stereotactic body radiotherapy (SBRT) is spreading worldwide as a new treatment modality for stage I NSCLC and oligometastasis [1][2][3]. Previous studies on SBRT for lung tumors have shown that dose escalations are desirable for improving local tumor control, considering overestimation of radiation doses by previously used dose calculation algorithms [4][5][6]. More precise dose calculation algorithms such as the Monte Carlo…”
Section: Introductionmentioning
confidence: 99%